Comparative Analysis of Assays for Detection of Cell‐Mediated Immunity Toward Cytomegalovirus and M. tuberculosis in Samples From Deceased Organ Donors. Issue 9 (10th July 2014) - Schmidt, T.; Schub, D.; Wolf, M.; Dirks, J.; Ritter, M.; Leyking, S.; Singh, M.; Zawada, A. M.; Blaes‐Eise, A.‐B.; Samuel, U.; Sester, U.; Sester, M.
<x xml:space="preserve">Abstract</x> Cell‐mediated immunity assays could be valuable for risk assessment of organ donors, but no data exist on their feasibility in deceased donors. In this study, 105 deceased donors (52.3 ± 16.9 years) were screened at the time of organ procurement. Pathogen‐specific stimulation was performed using a cytomegalovirus (CMV) lysate, tuberculin (purified protein derivative [PPD]) and soluble Mycobacterium tuberculosis‐specific ESAT‐6/CFP‐10 proteins in combination with an in‐house fluorescence‐activated cell sorting (FACS) assay or commercial assay formats (QuantiFERON‐CMV/TB for ELISA, T‐SPOT.TB for ELISPOT). CMV‐IgG antibody titers were determined as gold standard for CMV infection; 51.4% of samples were CMV seropositive. Indeterminate results were observed in 47.6% of ELISA, 12.5% of FACS and 0% of ELISPOT assays. Agreement with serology was highest for FACS (95.6%, κ = 0.91), followed by ELISPOT (84.0%, κ = 0.68) and ELISA (80.0%, κ = 0.60). Agreement between ELISA and serology increased if the CMV lysate was used as stimulus (96.7%, κ = 0.92). Among the T cell assays, agreement between ELISPOT and FACS was highest (κ = 0.70). PPD‐positive results among valid samples differed between assays (26.5% for ELISA, 23.1% for FACS and 50.5% for ELISPOT); 2.0% were QuantiFERON‐TB positive, 3.3% were ESAT‐6/CFP‐10‐positive in FACS and 13.4% were positive in the T‐SPOT.TB assay. In conclusion, cellular immunity may be analyzed from samples of deceased donors, although the assays differ in the rate of positivity and indeterminate results.